2008
DOI: 10.1021/pr800174k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Matched Primary and Metastatic Melanoma Cell Lines

Abstract: Identification of the biochemical pathways involved in the transformation from primary to metastatic melanoma is an area under intense investigation. A 2DE proteomics approach has been applied herein to the matched patient primary and metastatic melanoma cell lines WM-115 and WM-266-4, respectively, to better understand the processes that underlie tumor progression. Image analysis between samples aligned 470 common gel spots. Quantitative gel analysis indicated 115 gel spots of greater intensity in the metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…34,[36][37][38][39][40] In some cases, this upregulation has been associated with enhanced metastasis, radioresistance and poor clinical prognosis. 41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…34,[36][37][38][39][40] In some cases, this upregulation has been associated with enhanced metastasis, radioresistance and poor clinical prognosis. 41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Since tumor tissue is heterogeneous mixture of several cell types, cultured cell lines may be preferable for the screening of biomarkers. To search for biomarkers useful for the diagnosis of metastases, primary and metastatic cell lines were compared and several candidate biomarkers were successfully discovered (Table 4) (Bernard et al, 2003;Zuidervaart et al, 2006;Al-Ghoul et al, 2008). Proteomics analysis of melanoma-associated fibroblast stromal cells revealed the aberrant expression of several proteins not detected in normal fibroblasts (Paulitschke et al, 2009).…”
Section: Screening For Tumor Tissues and Cell Linesmentioning
confidence: 99%
“…68 CypA also regulates malignant transformation and metastasis. 81,85 Understanding the roles of CypA in cancer progression is critical to assessing its potential as a target for therapeutic intervention.…”
Section: Role Of Over-expressed Cypa In Cancersmentioning
confidence: 99%
“…CypB, which is mainly located in the ER lumen, is highly homologous to CypA. CypB possesses two antigenic epitopes (CypB [82][83][84][85][86][87][88][89][90][91][92] and CypB [91][92][93][94][95][96][97][98][99] ) recognized by HLA-A24-restricted 97 and tumour-specific cytotoxic Tlymphocytes, 98 and these peptides could be used for the development of anticancer vaccines. Over-expression of CYPB is associated with tumour progression through the regulation of hormone receptor expression and gene products involved in cell proliferation and motility.…”
Section: Other Cyps and Cancersmentioning
confidence: 99%